Automatic Marking about T-SQL Based on Oneway Close Degree - Chen, Huan Tong; Chen, Yao Fei; Zheng, Wei (Applied Mechanics and Materials, 2013)
This paper puts forward a method to realize TransactSQL (TSQL) automatic test paper evaluation, using oneway close degree to calculate the degree of similarity between the candidate answer and standard answer to realize automatic evaluation. And it introduces the grammar and structure of TSQL briefly, details the definition of oneway close degree, and analyzes and realizes the oneway close degree algorithm. The comparison of automatic marking and manual marking examples shows that, automatic marking is close to manual marking.